Effect of Covid-19 vaccine on some immunological salivary biomarkers (sIgA and Interleukine-17) - Ali, Dhuha M.; Taha, Ghada I. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: The most widely used vaccination against SARS-associated coronavirus (SARS-CoV-2) is the Pfizer vaccine, which provides protection against this virus. However, its ability to safeguard the oral cavity is unclear, and neither are the exact immunological biomarker levels it activates.Aim of the study: To investigate the possibility that Pfizer vaccination protects the oral cavity against Covid-19.Patients and Methods: The study group consisted of a total of 70 subjects (30 as the control group They were followed up before being vaccinated as non-vaccinated (maybe previously infected or non-infected or recovered) and 40 participants followed up three weeks after the first dose and one week after the second vaccination. All saliva samples were collected from the individuals in the current study at the medical city hospital in Baghdad from September 2021 to July 2022. The salivary biomarkers sIgA and IL-17 were detected by enzyme-linked immunosorbent assay (ELISA) kits.Result: Secretory IgA levels showed a highly significant difference (p0.05) in the followed-up group after the first vaccination compared to the non-vaccinated group (controls), however, a non-significant difference in its level was found in the followed-up group after the first vaccination compared to after the second vaccination. In contrast to healthy controls, non-vaccinated participants had greater salivary IL-17 levels. Followed-up participants’ IL-17 levels did not change significantly after the first and second vaccines (P>0.05).Conclusion: The Pfizer vaccine had a minor impact on sIgA because mRNA vaccines protect systemically more than salivary. Nevertheless, the Pfizer vaccine raises IL-17 levels after the first and second doses without triggering cytokine syndrome.